Clinicopathological features of gastric mucosa associated lymphoid tissue (MALT) lymphomas: high grade transformation and comparison with diffuse large B cell lymphomas without MALT lymphoma features. Issue 3 (1st March 2000) - Yoshino, Tadashi; Omonishi, Kunihiro; Kobayashi, Keita; Mannami, Tomohiko; Okada, Hiroyuki; Mizuno, Motowo; Yamadori, Ichiro; Kondo, Eisaku; Akagi, Tadaatsu
Abstract : Aims —To investigate the clinicopathological differences among gastric low grade MALT lymphomas (low MALT), large B cell lymphomas with low grade components (secondary high grade MALT lymphomas, high MALT), and diffuse large B cell lymphomas without low grade features (primary high grade MALT lymphomas, DLL). Methods —Clinicopathological and morphological characters of 126 gastric lymphoma cases were studied: 82 cases of low MALT lymphoma including 40 that were surgically resected, 17 cases of high MALT lymphoma including 13 surgically resected, and 27 cases of DLL including 12 surgically resected. Results —Age ranges were as follows: low MALT lymphoma, 34 to 85 years (mean 59.9); high MALT lymphoma, 53 to 88 years (mean 68.5); DLL, 29 to 83 years (mean 62.3). The average age for low and high MALT lymphomas was significantly different (p < 0.05), but there were no differences in other comparisons. There was a female predominance of low MALT lymphoma patients (female to male ratio, 47/35), while for high MALT patients the ratio was almost even (8/9), and for DLL patients there was a male predominance (11/16). Examination of surgically resected material showed that MALT lymphomas had a wider distribution in the gastric wall than DLL. Conclusions —The findings suggest that at least some of the high grade gastric lymphomas, especially in patients younger than the fifth decade, do not originate from high grade transformation of low MALT lymphomas. It seems to take about one decade at least for high grade transformation of low MALT lymphomas.